2019
DOI: 10.1016/j.neulet.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The signaling role for chloride in the bidirectional communication between neurons and astrocytes

Abstract: It is well known that the electrical signaling in neuronal networks is modulated by chloride (Cl) fluxes via the inhibitory GABA and glycine receptors. Here, we discuss the putative contribution of Cl fluxes and intracellular Cl to other forms of information transfer in the CNS, namely the bidirectional communication between neurons and astrocytes. The manuscript (i) summarizes the generic functions of Cl in cellular physiology, (ii) recaps molecular identities and properties of Cl transporters and channels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 220 publications
(169 reference statements)
2
43
0
Order By: Relevance
“…Finally, changes in Cl − concentration ([Cl − ] i ), induced by activation of Cl − ‐dependent transporters and/or Cl − channels are linked to activity‐related changes in the cellular volume of astrocytes (Chen & Sun, ; Kimelberg et al . ; Wilson & Mongin, ). The properties and functional role of Ca 2+ signalling has been extensively reviewed in the past, and in this paper we shall therefore focus on the signalling role of the other four major monovalent ions: Na + , Cl − , K + and H + .…”
Section: Ionic Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, changes in Cl − concentration ([Cl − ] i ), induced by activation of Cl − ‐dependent transporters and/or Cl − channels are linked to activity‐related changes in the cellular volume of astrocytes (Chen & Sun, ; Kimelberg et al . ; Wilson & Mongin, ). The properties and functional role of Ca 2+ signalling has been extensively reviewed in the past, and in this paper we shall therefore focus on the signalling role of the other four major monovalent ions: Na + , Cl − , K + and H + .…”
Section: Ionic Signallingmentioning
confidence: 99%
“…It has been shown that this directly facilitates their migration and infiltration in dense tissue (Ransom et al . ); (iii) modulation of several types of ion channels such as K + channels and TRPM7 channels through direct binding to yet uncharacterised channel protein domains; and (iv) regulation of intracellular signalling cascades such as WNK (With No lysine [K + ]) and serine/threonine protein kinases (see Wilson & Mongin, for details and relevant literature). At the same time astroglial [Cl − ] i may play an important role in maintenance and regulation of inhibitory transmission in the CNS.…”
Section: Astroglial Cl− – the Link To Cell Biology And Regulator Of Imentioning
confidence: 99%
“…12.1A). The low intracellular [Cl − ] compensates for the presence of the net-negatively charged macromolecules (e.g., proteins and polynucleotides) and numerous organic metabolites [see discussion in (Lang et al, 1998; Hoffmann et al, 2009) and the “neurocentric” view in (Wilson & Mongin, 2019)].…”
Section: Common and Unique Aspects Of Osmotic Balance Within The Cnsmentioning
confidence: 99%
“…The “classical” KCC1, KCC3, and KCC4 are silent under basal conditions but are activated by increases in cell volume, while the neuron-specific KCC2 is basally active and additionally stimulated by cell swelling (Lauf & Adragna, 2000; Gamba, 2005). The contribution of KCCs to neuronal cell volume control has been suggested in the past but never definitively tested (Kahle et al, 2015; Wilson & Mongin, 2019). In one study, cultured hippocampal pyramidal neurons from KCC3-null mice showed a lack of RVD in hypoosmotic media (Boettger et al, 2003).…”
Section: Rvd In the Cns Cellsmentioning
confidence: 99%
“…The inattention to Clmay be traced back to the pioneering work on neuronal action potentials by Hodgkin and Huxley, who characterized Clas responsible for only minor "leak" currents 1 . While it is now recognized that Clmovement is critical for homeostatic functions in the brain, including regulation of cell volume and pH [2][3][4][5][6] , the role of Clin excitability remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%